2007
DOI: 10.1055/s-2007-1091106
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Granular Cell Tumor of the Skull Base

Abstract: Objective and Importance: Malignant granular cell tumors (MGCTs) are extremely rare, high-grade sarcomas of Schwann cell origin. They often metastasize and are associated with short survival. We describe a patient with a large MGCT arising from the suboccipital nerve that eroded the posterior skull base, invaded the perifocal neck muscles, demonstrated perineural extension, and metastasized to regional lymph nodes. Clinical Presentation: A 60-year-old woman with several years' history of neck pain noticed a ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…In a review of 53 metastatic GCT cases, bone metastases were reported in 9 cases . There has also been 1 case report of malignant GCT arising from the suboccipital nerve and eroding the posterior skull base . However, there had been no reports of primary GCT arising within the bone, making the present case the first report of a primary intraosseous GCT.…”
Section: Discussionmentioning
confidence: 64%
“…In a review of 53 metastatic GCT cases, bone metastases were reported in 9 cases . There has also been 1 case report of malignant GCT arising from the suboccipital nerve and eroding the posterior skull base . However, there had been no reports of primary GCT arising within the bone, making the present case the first report of a primary intraosseous GCT.…”
Section: Discussionmentioning
confidence: 64%
“…Although a few cases of GCT with perineural involvement and a plexiform growth pattern have been described in the literature, none of them were treated with MMS 37–40 . In 1994, Lee and colleagues published a report of two cases of “a previously undescribed variant of GCT with an interesting plexiform pattern.” 41 One case was found on the lower leg of a 10‐year‐old girl, and the other was on the back of a 12‐year‐old girl.…”
Section: Discussionmentioning
confidence: 99%